A Systematic Review of Section 1983 Lawsuits Filed by Texas Inmates. Issue 3 (27th May 2022) - Palacios, Jazmin E.; Butler, H. Daniel; Griffin, O. Hayden
ABSTRACT: Despite considerable change in inmate rights over the past several decades, researchers, practitioners, and policymakers know little about the current state of prisoner litigation. The purpose of this study is to examine the conditions of confinement within Texas prisons that inmates allege violated their constitutional rights by examining federal court rulings decided in 2015. We performed a systematic review of 121 cases to identify themes and patterns that can inform policy and practice. The findings from our study indicate most lawsuits are unsuccessful, and that most lawsuits allege violations related to due process rights.